The influence of follicular fluid on the regulation of apoptosis and related genes during IVM of camel oocytes - A.A. Ammari; AR. Alhimaidi; K.N. Yaseen; B.O. Almutairi; R.A. Amran; A. AL-juaimlan; A. Rady (Arquivo Brasileiro de Medicina Veterinária e Zootecnia)
ABSTRACT Follicular fluid is a haven that provides a microenvironment for the development and maturation of oocytes. It is a medium that provides a means of communication within the follicular cells. The role of follicular fluid in the development and maturation of follicles and oocytes involves the actions of certain genes. Here, we examined the impact of CFF on the gene expression of camel oocytes during (IVM). Hypothetically, IVM medium was enhanced with 2.5% CFF, and we analyzed the expression of several genes including Bax, Bcl-2, P53, Acta2, TGFβ, Cx43, and Tagln. Consequently, the follicular fluid from camels had a substantial effect on the mRNA transcript level of the BCL2 gene, which is related to apoptosis. Acta2 and Tagln genes that relate to cytoskeletal protein “actin” in transforming growth factor beta (TGFβ) pathway were also modulated. However, the follicular fluid increased the expression of TGFβ in camel oocytes. This study showcases the beneficial effects of CFF on camel oocyte Gene Expression and provides a platform for studying the many mechanisms involved in oocyte meiosis, particularly those associated with the TGFβ pathway. We recommend using higher dosage and measuring the expression levels of certain genes involved in programmed cell death and inflammation.